2004
DOI: 10.1029/2003gl019059
|View full text |Cite
|
Sign up to set email alerts
|

On the role of vibrationally excited H2 as a source of OH in the mesosphere

Abstract: [1] It has recently been suggested that the reaction between vibrationally excited H 2 (v = 1) and O( 3 P) atoms may be an important source of OH in the upper mesosphere. Here, we report accurate quantum calculations of rate coefficients for the O( 3 P) + H 2 (v = 1) reaction and show that the proposed mechanism is not an important source of OH in the mesosphere. Our calculation employs chemically accurate potential energy surfaces for the O + H 2 system and quantum mechanical method for the calculation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…18 Owing to this experimental breakthrough and the availability of new ab initio PESs of chemical accuracy, 16,22 there currently is a renewed theoretical interest in the title reaction. 3,[18][19][20][21][22][23] Recently, Braunstein et al 20 reported the excitation function for O͑ 3 P͒ +H 2 ͑v =0−3, j =0͒ → OH+ H calculated with the quasiclassical trajectory ͑QCT͒ and time-dependent quantum-mechanical ͑TDQM͒ scattering methods on the PESs of Rogers et al 16 QCT reaction cross sections for H 2 ͑v Ͼ 0͒ were found to overestimate TDQM results by as much as a factor of Ϸ2 near threshold, although the agreement is gradually restored as the collision energy is increased. Using the same PESs, time-independent coupled-channel quantum scattering calculations by Balakrishnan 21 obtained cross sections in close agreement with the experiment and TDQM results.…”
Section: Introductionmentioning
confidence: 97%
“…18 Owing to this experimental breakthrough and the availability of new ab initio PESs of chemical accuracy, 16,22 there currently is a renewed theoretical interest in the title reaction. 3,[18][19][20][21][22][23] Recently, Braunstein et al 20 reported the excitation function for O͑ 3 P͒ +H 2 ͑v =0−3, j =0͒ → OH+ H calculated with the quasiclassical trajectory ͑QCT͒ and time-dependent quantum-mechanical ͑TDQM͒ scattering methods on the PESs of Rogers et al 16 QCT reaction cross sections for H 2 ͑v Ͼ 0͒ were found to overestimate TDQM results by as much as a factor of Ϸ2 near threshold, although the agreement is gradually restored as the collision energy is increased. Using the same PESs, time-independent coupled-channel quantum scattering calculations by Balakrishnan 21 obtained cross sections in close agreement with the experiment and TDQM results.…”
Section: Introductionmentioning
confidence: 97%
“…An effective method for accelerating chemical reactions is excitation of vibrational or electronic degrees of freedom of reactive molecules. Experimental data show that molecules excited even to the lowest vibrational or electronic states react 10-100 times faster than unexcited ones [1][2][3][4]. The burning of the most combustible mixtures occurs through the mechanism of chain-branching reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Product State Distributions. The calculated product OD/OH vibrational distributions for the title reactions on the 3 A″ state are also shown in Figure 3, which are obtained by summing all available rotational state populations in each vibrational channel. In the energy range considered, v′ = 0, v′ = 1, and v′ = 2 vibrational levels of the OH/OD molecule are open.…”
Section: Resultsmentioning
confidence: 99%
“…23 Recently, several authors 23,[28][29][30]39 reported that, when the collision energy is higher than 1.0 eV, the ICSs obtained from a full calculation with a complete model that include non-Born−Oppenheimer coupling between all PESs differ by at most 10% from independent single PES calculations. When the considered collision energy is below 1.0 eV, recent QCT studies 21,23,30 of surface-hopping effects between O( 3 P) + H 2 and O( 1 D) + H 2 reactions have shown that the dynamics properties can be accurately described by single surface calculations on 3 A′ and 3 A″ PESs. The above argument is further supported by the fact that the ICSs obtained from recent crossed molecular beam measurements 11 are in a good agreement with the calculation results on the singlet PES 3 A′ and 3 A″.…”
Section: Theoretical Methodsmentioning
confidence: 97%